Enhancing online learning environments through real-time social presence dashboards: Insight from expert focus groups - Norz, Lisa-Maria; Schmelzer, Dorothea; Ammenwerth, Elske (Proceedings of the International Conference on Networked Learning, 2024)
Online learning is promoted to play a pivotal role in the future of education, necessitating a focus on student engagement and interactivity as essential components for successful online educational environments. Social presence, as a construct capturing these social aspects, is extensively recognized, and investigated within the realm of education and widely shaping the online learning experience. However, a crucial gap remains in the absence of a real-time measurement of social presence. Drawing from prior research, this study identifies indicators derived from social network analysis as promising metrics for assessing social presence in online learning environments. What remains unclear is the means to effectively convey this information to instructors, enabling them to enhance the educational online experience. To address this gap, we conducted focus groups involving seven experts in online education and pedagogical expertise. Our findings reveal that the development of a social presence dashboard holds immense potential for enriching the online teaching experiences through the utilization of these identified indicators. Furthermore, incorporating additional visualizations and graphical representations with such dashboards can equip online instructors with the necessary insights to foster social interactions and capture real-time social dynamics within online courses. However, the implementation of such dashboards necessitates a careful consideration of important ethical and practical considerations, including informed consent procedures, student monitoring practices, and adherence to ethical standards. This research contributes valuable insights into the ongoing discourse on improving online education by leveraging technology to enhance social presence and pedagogical effectiveness.